Analysis of the students’ enrollment rate at the School of English and Pedagogy of the Arts and Humanities Faculty. - Acurio Orozco, Juan Andrés (2018)
In the latest years, the School of English at the UCSG has seen its number of students reduced substantially. This represents a problem not only for the university, but for the students as well. Some of the problems that derive from this situation are: little flexibility in the schedules, longer times to graduate and lower payment for part-time teachers. In order, to explore the situation at the School of English and identify possible reasons that might be causing this problem, a number of research instruments have been adapted. By conducting a survey at two high-schools from different social classes, it has been possible to discern what students think about being a teacher. Moreover, surveys applied to former students of the School of English as well as students from first semester have been useful for identifying what reasons they have for dropping out of the career. Additionally, an interview with Prof. John Gonzalez, director of the School of English, was scheduled to analyze how the authorities have approached this problem. Findings show that the majority of high-school students do not consider education as their first option when choosing a career. They would rather study Medicine, Marketing or become entrepreneurs. Additionally, it was possible to identify that the two major reasons for the shortage of students are lack of promotion and high prices. Finally, authorities believe that money is a key factor in the issue of low enrollment.